2022
DOI: 10.3389/fcvm.2022.907747
|View full text |Cite
|
Sign up to set email alerts
|

GSK-J4, a Specific Histone Lysine Demethylase 6A Inhibitor, Ameliorates Lipotoxicity to Cardiomyocytes via Preserving H3K27 Methylation and Reducing Ferroptosis

Abstract: Changes in modern lifestyle provoke a series of metabolic stresses such as hyperlipidemia. Excessive free fatty acids induce cardiomyocyte metabolic reprogramming and rearrangement of the lipid content of cardiomyocyte and promote oxidative stress. As a newly defined lipid peroxidation-related cell death pathway, the role of ferroptosis in metabolic stress-induced cardiomyocyte injury is poorly revealed. Our work indicates that GSK-J4, a histone lysine demethylase 6A/6B dual inhibitor, can alleviate palmitic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…A significant accomplishment of this study is the novel application of existing epigenetic drugs for treating meniscus tear injuries. Our selected drug candidates, GSKJ4 (a histone demethylase inhibitor) [31][32][33][34] and C646 (a histone acetyltransferase inhibitor) [35][36][37] effectively restored the migration speed of the inner meniscus cells under TNF-α treatment. This aligns with prior research suggesting that inflammatory cytokines activate JMJD3 via the NF-kB pathway, diminishing…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant accomplishment of this study is the novel application of existing epigenetic drugs for treating meniscus tear injuries. Our selected drug candidates, GSKJ4 (a histone demethylase inhibitor) [31][32][33][34] and C646 (a histone acetyltransferase inhibitor) [35][36][37] effectively restored the migration speed of the inner meniscus cells under TNF-α treatment. This aligns with prior research suggesting that inflammatory cytokines activate JMJD3 via the NF-kB pathway, diminishing…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we employed GSKJ4, an inhibitor of the H3K27me3 demethylase JMJD3, known to elevate the overall level of H3K27me3 in cells [31][32][33][34] , and C646, an inhibitor of the histone acetyltransferase p300, which reduces the overall level of histone acetylation [35][36][37] .…”
Section: Inner Meniscus Cellsmentioning
confidence: 99%
“…For example, it has been demonstrated that metformin and GSK-J4 may ameliorate lipotoxicity to cardiomyocytes via ferroptosis. 23 , 29 Quercetin, which decreases the expression of ATF3, could alleviate acute kidney injury via inhibition of ferroptosis. 30 Overall, ferroptosis might play an important role in PA-treated endothelial dysfunction and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Yu et al demonstrated that EZH2 mitigated the ferroptosis of tongue squamous cell carcinoma cells by suppressing miR-125b-5p but upregulating SLC7A11 expression 203 . Additionally, GSK-J4, a dual inhibitor of histone lysine demethylase 6A/6B that prevents H3K27 demethylation, can suppress palmitic acid (PA)-induced hypersensitivity to ferroptosis by inhibiting ACSL4 expression and lipid peroxidation in cardiomyocytes 204 . KMT2B activated the transcription of riboflavin kinase (RFK) by enhancing the trimethylation of H3K4, which subsequently accelerated tumor necrosis factor-α (TNF-α)/NADPH oxidase 2 (NOX2) axis activation to promote ferroptosis during myocardial ischemia/reperfusion injury 205 .…”
Section: Protein Methylation In Ferroptosismentioning
confidence: 99%